Disaster Resilience Through Social Capital Among Indonesian Migrant Workers in Taiwan - Zulianto, Mukhamad; Herlindawati, Dwi; Triyono, Bambang; Sari, Nia Devita; Masduki, Damayanti (Bina Nusantara University, 2026)
This research examines how Indonesian Migrant Workers (IMWs) in Taiwan build disaster resilience by mobilizing social capital, particularly in contexts where formal institutional support is limited or absent. Using an interpretive qualitative approach, the study adopts a case study design that includes semi-structured interviews and participant observation. The findings reveal that bonding and bridging social capital, developed through informal community connections, digital platforms, and shared religious and cultural practices, serve as critical assets for disaster preparedness and response. These networks enable mutual aid, timely information exchange, and collective action among IMWs during disaster situations. However, linking social capital appears weak, indicating limited engagement with formal institutions and restricted access to public resources and legal protections. Informal leadership structures and culturally rooted coping strategies continue to play a significant role in fostering grassroots resilience. Nonetheless, systemic challenges such as language barriers, precarious legal status, and digital exclusion continue to impede broader institutional integration. By highlighting the experiences and agency of IMWs, this research contributes meaningfully to the discourse on disaster governance. It underscores the importance of inclusive frameworks that acknowledge the capabilities of migrant communities as active disaster actors rather than passive recipients of aid. It advocates for the inclusion of community-based organizations in national disaster policies and recommends comparative studies across different migrant-receiving contexts to deepen understanding of transnational resilience dynamics.